Performance Analysis of 3 Phase Induction Motor Against Loading Using the Power Simulator (PSIM) Application - Muhamad Soleh; Taryo Taryo; Arifudin Arifudin (Mestro, 2022)
Three-phase induction motors are the most widely used type of motor in industry, induction motors are widely used as prime movers to turn loads on production machines in the industrial world. The output of a three-phase induction motor is the amount of torque to move the load. If the load torque carried by the three-phase induction motor is greater, then the three-phase induction motor will not rotate. And if the load torque carried by a three-phase induction motor is too small, this is considered excessive. In this analysis the method used by the author is the experimental method of analysis using the Power Simulator application with load data and induction motor data. Based on the analysis, it was found that Istart and Inominal on a 15 kW induction motor have different values ​​according to the torque value used, so the torque value is directly proportional to the Istart value. Meanwhile, Istart induction motors 15 kW 894.324 (15 N.m), 894.149 (25 N.m), 894.159 (60 N.m) and 45 kW induction motors 355.15 (25 N.m), 355.172 (60 N.m), 355.172 (80 N.m) and induction motors 55 kW 337.743 (30N.m), 337.76 (50N.m) and 337.761 (100N.m) Reaches 80% of full speed, torque is at its highest “pull-out torque”) and current starts to fall and is at full speed, or synchronous speed, torque and stator currents drop to zero, it can be concluded that the greater the value of the stator resistance, the smaller the value of the starting current. Keywords: Induction Motor, Torque, PSIM